2010
DOI: 10.1002/anie.201004974
|View full text |Cite
|
Sign up to set email alerts
|

Liquid‐Crystal Templating in Ammonia: A Facile Route to Micro‐ and Mesoporous Metal Nitride/Carbon Composites

Abstract: Templation in liquid ammonia: The first porous materials formed by templating in liquid ammonia utilize the liquid‐crystalline phase formed by cellulose/NH4SCN in NH3. By changing the proportions of reactants, the porosity, surface area, and morphology of the materials can be modified. The as‐synthesized mesoporous materials present a lamellar morphology (see picture).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0
3

Year Published

2014
2014
2018
2018

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 48 publications
1
19
0
3
Order By: Relevance
“…As was expected, after high-temperature annealing in amonia atmosphere, three diffraction peaks at 37°, 44°, and 63° appear and correspond well to the face-centered cubic (fcc) TiN (111), (200), and (220), respectively (JC-PDS, #65-0715) which is identical to previous work. [ 27,48 ] Same characterization was conducted to the anode material. (101) and (211).…”
Section: Doi: 101002/adma201501838mentioning
confidence: 99%
“…As was expected, after high-temperature annealing in amonia atmosphere, three diffraction peaks at 37°, 44°, and 63° appear and correspond well to the face-centered cubic (fcc) TiN (111), (200), and (220), respectively (JC-PDS, #65-0715) which is identical to previous work. [ 27,48 ] Same characterization was conducted to the anode material. (101) and (211).…”
Section: Doi: 101002/adma201501838mentioning
confidence: 99%
“…It was found that nanocellulose fibrils can self‐organize into the nematic liquid‐crystalline mesophase not only in water, but also in a NH 3 /NH 4 SCN mixture . This system was employed to prepare nitrides of titanium and vanadium through its mineralization by tetrakis(diethylamido)titanium(IV) or vanadium tetrachloride and subsequent calcination at 600 °C under a flow of NH 3 .…”
Section: Applicationsmentioning
confidence: 99%
“…[71] Abhängig von der Cellulosekonzentration wurde eine LC-Phase (ca. [71] Abhängig von der Cellulosekonzentration wurde eine LC-Phase (ca.…”
Section: Charakterisierungstechnikenunclassified
“…B. Glucose) zur CNC-Dispersion vor der EISA die Kinetik des Sol-Gel-Härtens verändert [76] und zu großen, rissfreien [30,42,71,74] Flüssigkristalline Template Angewandte Chemie Kompositfilmen führt. Kelly et al fanden, dass die Zugabe einfacher Polyole (z.…”
Section: Charakterisierungstechnikenunclassified
See 1 more Smart Citation